Implementasi Model Pembelajaran Teams Games Tournaments untuk Meningkatkan Hasil Belajar IPA dalam Tema Makanan Sehat di Kelas V SD Negeri Nafar - Gerson, Dina; Pelamonia, J.; La Sitiman, Hediaty (Universitas Pattimura, Program Studi Diluar Kampus Utama (Program Studi Pendidikan Guru Sekolah Dasar), 2022)
The problem in this research is that the learning outcomes of class V students are not optimal in thematic learning theme 3 sub theme 1 ''how the body processes food''. This happens because the learning process does not involve students optimally, learning tends to be conventional models. This research was carried out with the aim of knowing (1) improving learning outcomes by using the Teams Games Tournament (TGT) model in thematic subjects of theme 3 sub-theme 1